The Impact of Islamic Fintech on Poverty Alleviation in Indonesia: A Socio-Economic Implications - Tegar Rismanuar Nuryitmawan (Airlangga Journal of Innovation Management, 2023)
Poverty alleviation remains a critical focus in Indonesia's agenda alongside technological advancement. The establishment of an inclusive Islamic financial ecosystem, integrating digital financial services (fintech), stands as a significant initiative. However, challenges including regulatory inadequacies, complex licensing, misuse in terrorism financing, and consumer disputes plague this evolving landscape. This study investigates the impact of Islamic fintech on poverty reduction from 2005 to 2022, utilizing an Ordinary Least Squares (OLS) model. Results indicate that Islamic fintech interventions exhibit promise in mitigating poverty while strengthening the financial system. This underscores the pivotal role of the financial infrastructure in societal welfare development. Compared to mere economic growth, Islamic fintech demonstrates potential for sustained socio-economic development, particularly aiding Shariah-compliant enterprises seeking expansion. The findings emphasize the necessity of addressing regulatory intricacies to fully harness the transformative potential of Islamic fintech. This study underscores the significance of fostering an enabling regulatory environment, contributing to Indonesia's long-term socio-economic development and poverty alleviation strategies.